Estimation of Safe Speed Limit along Urban Roads of Developing Countries: A Simplified Approach - PRAMANIK, Sankhadeep; CHAKRABORTY, Sandip; ROY, Sudip Kumar; SEN, Saptarshi (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Unreasonable speed limits caused by the lack of coordination between operating speed and posted speed limit can be a major contributor to traffic accidents. A number of vulnerable road users have increased in the urban traffic stream than before. Therefore, on some roads speed limit imposing authority may have to revise the speed limits in such a way so that it will be safe for every road user. Considering general tendency of driver to drive above the speed limit, an approach was given to revise the speed limit so that even if driver drove above the speed limit but still it will be within safe limit. Relationships between speed limits and operating speeds, operating speeds and flow rates were developed. Finally based on regression models a simplified approach is proposed to revise the speed limit value based on existing traffic parameters from the safety point of view.